The Holocene paleolimnology of Lake Issyk-Kul, Kyrgystan: trace element and stable isotope composition of ostracods - Ricketts, R. D.; Johnson, T. C.; Brown, E. T.; Rasmussen, K. A.; Romanovsky, V. V. (Paleogeography, Palaeoclimatology, Palaeocecology, 2001)
The stable isotope and trace element geochemistry of ostracode shells from Lake Issyk-Kul, Kyrgyzstan, provide an important new paleoclimate record for central Asia. The δ18O, δ13C, Sr/Ca, Mg/Ca and U/Ca composition of shells from the species Candona neglecta found in two piston cores constrains the paleohydrology of the lake from 8700 to 1000 calendar yr before present. These data, combined with robust chronologies based on 16 AMS 14C dates, suggest that the region went from a relatively moist climate in the early Holocene to a more arid climate in the late Holocene. Intense freshwater input, presumably glacial runoff, flowed into the lake from 8700 to 8300 cal yr BP as evident from the δ18O and δ13C values. From 8300 to 6900 cal yr BP δ18O and Sr/Ca values indicate that the lake was relatively fresh and an open basin, and U/Ca values suggest that the lake was well-mixed with well-oxygenated bottom waters. There is a transition zone between 6900 and 4900 cal yr BP when δ18O and Sr/Ca values rapidly increase and Mg/Ca and U/Ca values rapidly decrease. During this period the lake evolved from an open, freshwater, well-mixed lake to a closed, more saline, less well-mixed lake. For the remainder of the record δ18O, Sr/Ca, Mg/Ca and U/Ca are relatively constant, implying conditions similar to modern conditions, although the slight increasing trend in Sr/Ca may suggest an increase in salinity over this period. The δ13C values were approximately in equilibrium with atmospheric CO2 in the early part of the record but became relatively negative in the later part of the record. This indicates that the dominant mechanism controlling the isotopic composition of dissolved inorganic carbon shifted from exchange with the atmosphere to variations in biological productivity.
id: 341